Increasing Legal Awareness of Village Communities Through an Integrated Legal Counseling Program: A Case Study of Pasir Angin Village - Samosir, Tetti; Maslihati Nur Hidayati; Didi Sunardi; Kevin Malinowski Simanjuntak (PT Inovasi Pratama Internasional, 2025)
Legal awareness among rural communities remains relatively low due to limited access to legal information and minimal outreach from authorities. This study aims to analyze the effectiveness of the implementation of an integrated legal outreach program in increasing legal awareness among the people of Pasir Angin Village. The study used a qualitative approach with a case study design and participatory action research involving 87 participants from various community groups over a six-month period. Data collection was conducted through participant observation, in-depth interviews, focus group discussions, and document analysis, then analyzed using thematic analysis techniques. The outreach program integrated five main topics: land and electronic certificates, narcotics prevention, personal data protection in fintech, family and inheritance law, and notary aspects. The results showed a significant increase in the level of community legal understanding from an average of 34% to 78%, with a program satisfaction level reaching 4.3 on a scale of 5. This program successfully shifted the community's paradigm from a traditional approach to a more structured formal legal settlement. Key success factors included the competence of the resource persons, interactive-participatory delivery methods, village government support, and the relevance of the material to the real needs of the community. This research provides an important contribution to the development of a community service model in the legal field and can be replicated in other villages with adjustments to the local context to create a more legally aware community and able to access justice optimally.